PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA BERDASARKAN TAHAPAN POLYA SISWA KELAS VIII MTs NEGERI 5 LOMBOK TENGAH TAHUN AJARAN 2024/2025 - Sabti Hajjatul Khotimah; Laila Hayati; Eka Kurniawan; Ketut Sarjana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACTThis research aimed to determine the effect of the guided inquiry learning model on students problem solving ability in class VIII at MTs Negeri 5 Lombok Tengah for the academic year 2024/2025. Research with a quantitative approach that uses a quasi- experimental design, the experimental class learning using the guided inquiry learning model while the control class using direct learning. The population in this study was 5 class VIII students. The samples were taken using a simple random sampling technique, resulting in class VIII A as the experimental class and VIII B as the control class. Data collection was carried out using problem solving ability test questions. From the research results, it was found that there were differences between the experimental class and the control class. Judging from the average score of the experimental class 82,41 and the control class 73,81, this shows that the problem solving ability of the class whose learning uses guided inquiry is better than the class whose learning uses direct learning. The effect size test results obtained were 0,810, which is in the high category. So it can be concluded that there is an effect of the guided inquiry learning model on mathematical problem solving in class VIII of MTs Negeri 5 Lombok Tengah in the high category.